Tooth Wear Epidemiology and Its Associated Periodontal Health and Sociodemographic Factors in a Cluster of Senior Citizens in Northern Greece - Charis Theodoridis; George Menexes; Vasiliki Topitsoglou; Sotirios Kalfas (MDPI AG, 2022)
Tooth wear (TW) is an irreversible and cumulative phenomenon causing aesthetic and functional compromise. Increasing wear has been associated with age, and various other factors have been reported to influence its type and/or severity both in individuals and groups. Increased TW may constitute a major future problem for the elderly. The present cross-sectional study aims at determining the prevalence of TW in senior citizens from Northern Greece and evaluating the patient-level associations between TW, periodontal condition, and sociodemographic factors. A sample of 363 dentate individuals, aged between 65 and 74 years, was considered according to the WHO guidelines for national pathfinder surveys and three different dentists examined the representative population groups from different urban and rural areas in Northern Greece. The examiners were calibrated prior to the survey, with an interexaminer agreement of over 85%. The simplified TWI, community periodontal index (CPI), attachment loss (AL), plaque index (DI), calculus index (CI), and sociodemographic factors were detected and measured. TW is very prevalent among senior citizens in Northern Greece, with males having been found to experience more wear. Age and oral health status, when measured by the periodontal indices AL, DI, and CI, are significantly combined with TW in both urban and rural areas.